Development of guidance and counseling modules to improve students' skills in responding - Sri Rahayu Wardani; Daharnis Daharnis (International Journal of Applied Counseling and Social Sciences, 2022)
Students’ activities in class are very diverse when participating in the learning process, sometimes students do not dare to argue or are passive in class. This is indicated by the low activeness of students in responding when learning activities take place. The aims of this research are: (1) to produce a guidance and counseling module to improve students' skills in responding to valid ones, (2) to produce a guidance and counseling module to improve students' skills in responding which are practical to use, and (3) to produce modules guidance and counseling module to improve students' skills in responding effectively.The research method used is development research by following the development steps of ADDIE model. The subjects of the research trial consisted of three experts to test the module validity, four GC  teachers or counselors to test the module practicality and 35 students to test the module effectiveness. The research data were analyzed using descriptive analysis and nonparametric statistics.The results showed that: (1) the guidance and counseling module to improve students' responding skills was in the valid category, (2) the practical level of the guidance and counseling module to improve students' responding skills which was developed was in the very high category, (3) the guidance and counseling module to improve students' skills in responding effectively to improve students' responding skills. Thus, the guidance and counseling module developed is valid, practical and effective and can be used by GC teachers or counselors to improve students' skills in responding